"Railway Work, Life & Death": Exploring British and Irish Railway Worker Accidents, c. 1890–1939. (1st November 2020) - Esbester, Mike
Abstract : The "Railway Work, Life & Death" project explores accidents and ill-health amongst British and Irish railway workers from the late nineteenth century to 1939. Drawing from state, railway company and trade union records, the project is making details of the working lives and accidents of railway employees more easily accessible. This note describes the collaborative impetus behind the project, and the crowd-sourcing methodology used, including the importance of working with volunteers. It shows that focusing on individual cases, at scale, is extremely revealing about the nature of work and the dangers of one of the largest employers of its time. It aims to encourage others to engage with crowd-sourcing and co-creation, as well as to make use of the resources being produced.